COVID-19: Is herd immunity the answer? - Robinson, Jared; Banerjee, Indrajit; Sathian, Brijesh (Journal of Advances in Internal Medicine, 2020)
The current global figures of COVID-19 is still rising. Many countries have enforced lockdowns to safeguard its citizens, however in most cases this has been to the dire detriment of the economy. Most leaders and governments have been holding out and looking to the development of a vaccine to be the answer to this COVID-19 pandemic, however at this point in time and for the foreseeable future a viable and widely available vaccine is not likely to be developed. In juxtaposition to the conventional methods countries such as Singapore, Israel, Iceland, Portugal, The Netherlands, Sweden, Hong Kong, Japan, South Korea, Indonesia, Taiwan and Turkey have adopted the concept of herd immunity. It is there for poignant and of the upmost importance that an alternate stratagem is developed and exercised to best facilitate the re-ignition of the country’s economy as well to best protect its citizens from the virus. Models such as herd immunity or a model based thereon are the most logical solution to attain this goal. At this time in the development of the global COVID-19 pandemic it is too early to conclude as to whether a fully-fledged lockdown is more effective and useful than the establishment of herd immunity. In order to achieve the goal of safeguarding the lives of a countries citizens as well as its economy, a mixed method of lockdown and herd immunity is advised. Individuals who are economically active and less susceptible to the virus should adopt the herd immunity model, whereas those who are elderly with concomitant comorbidities should exercise self-isolation and follow the lockdown model. The application of using both models simultaneously, will both capitalize on the advantages of either and negate the drawbacks thereof. This ultimately decreasing the loss of lives whilst still inducing a degree of herd immunity within the general populous.